Value relevance of alternative methods of accounting for actuarial gains and losses - Morais, A. I. (2011)
In 2010, IASB published an exposure draft about defined benefit plans where it proposed to eliminate the deferred recognition of actuarial gains and losses. IASB aimed to make fundamental improvements to the recognition, presentation and disclosures of defined benefit plans by mid-2011. To shed light on the debate on the recognition of actuarial gains and losses of defined benefit plans, this paper investigates the value relevance of financial information under three alternative methods of recognising actuarial gains and losses allowed by IAS 19: employee benefits (2004): the profit or loss method, the equity recognition method and the corridor method. Findings suggest that the equity recognition method, i.e., the recognition of all actuarial gains and losses in equity, best reflects the market’s valuation of actuarial gains and losses of defined benefit plans.